A multiple case study of the design of waiting areas in selected shopping malls in Metro Manila using the theory of proxemics - Duarte, Reisha Mae C.; Mayo, Adelaida Villaraza (Quezon City College of Home Economics, University of the Philippines Diliman, 2013)
ABSTRACT Shopping malls and their varying priorities, intentions, and target markets have resulted in a difference in design and featured facilities to better cater to the different lifestyles that are prominent in Philippine modern society today. This multiple case study sought to discover how differently designed shopping mall waiting areas affect the distances people maintain between themselves and others. Three (3) waiting areas located in three (3) different shopping malls unique from each other in terms of target market, accessibility, and design were selected through non-probability convenience sampling. Using an observation checklist the waiting areas were evaluated and analyzed in the context of the Theory of Proxemics. To supplement the data gathered from observation, the preferences of Filipinos regarding waiting areas in malls were obtained through an online questionnaire. The results of this study showed that different classes of malls provided uniquely designed waiting areas. This suggests their differing intentions and priorities. Results showed that the design of these waiting areas greatly affects how people perceive these spaces and their behavior while using them. Likewise, the findings revealed that the interior design of waiting areas in malls may either encourage and discourage certain behavioral patterns among users of those spaces. Further studies for researchers who wish to pursue a similar topic are recommended to tackle a wider scope-one with more defined variables in terms of observation days, hours, and times of the day. It is also recommended that an equal number of participants from each category (based on gender, age, financial capability) be selected and included in their study.
Thesis (BSID)--University of the Philippines Diliman.
Keywords: Waiting rooms -- Philippines; Shopping malls -- Philippines -- Decoration